Analisis Yuridis Cerai Gugat Dengan Alasan Perselingkuhan Di Pengadilan Agama Praya Kabupaten Lombok Tengah: Studi Putusan PA Praya Nomor 1071/PD.G//2020/P1.Pra - Lale Dita Ayu Liantari; Sahruddin Sahruddin (Fakultas Hukum Universitas Mataram, 2022)
This research’ aims are to know Islamic law and positive law perspectives on the verdict of Praya Islamic Court Number 1071/Pdt.G/PA.Pra on divorce because of an affair also to know judge’s consideration in the verdict Number 1071/Pd.G/2020/PA.pra Praya Islamic Court, Central Lombok whether if it has been align with the binding laws. This research applies normative legal research. research’ result shows that according to Indonesian positive laws and Islamic Compilation Law also judge’s consideration reviewed with Law Number 1 of 1974 on Marriage Article 39 letter (f), and Article 115 and 116 Islamic Compilation Law .